"If I Am Straight You Are Askew": Labelling Heterosexuals as Straight Worsen Gay Men's Perception. Issue 1 (2nd January 2021) - Sacchi, Simona; Brambilla, Marco; Spaccatini, Federica; Giovannelli, Ilaria; Pacilli, Maria Giuseppina; Pagliaro, Stefano
ABSTRACT: A robust stream of research has shown the detrimental influence of slurs and derogatory epithets on attitudes toward minority groups. Extending prior work, we explored the influence of positive labels ascribed to the majority group on the evaluation of the minority group. Specifically, three studies tested the possibility that the label "straight, " generally linked with the concept of morality, would promote a negative evaluation of gay men. Study 1 exposed English speakers to an individual person described as straight (vs. heterosexual) while Study 2 exposed English speakers to a target person described as straight (vs. heterosexual vs. no label). Study 3 considered a non-English sample (i.e., Italian adults) and experimentally induced the association between the straight label and the concept of heterosexuality. In each study, participants were asked to express their attitudes toward a gay target after the manipulation. Results showed that heterosexual participants exposed to the label "straight" reported more negative attitudes toward gay men than heterosexual participants exposed to the label "heterosexual" (or when they were not exposed to any label). Critically, such an effect emerged only among highly religious participants. Implications for policies and prejudice reduction are discussed.